Bifurcation of fiber reinforced inflated membranes with different natural configurations of the constituents - Heiko Topol (14156889) (2023)
This article studies the inflation and bulging of fiber‐reinforced hyperelastic membranes. A neo‐Hookean model describes the mechanical behavior of the ground substance, and a relatively standard reinforcing model describes the mechanical behavior of fibers. The natural configuration of the constituents may differ, for example, because the fiber may be pre‐stretched in comparison to the natural configuration of the ground substance. Additionally, the fibers may be dispersed. Both the pre‐stretch and dispersion of the fibers have an effect on the formation of a bulge. The results explore how material stiffness ratios and fiber arrangements are involved in initiating bulging instabilities. The herein presented results may provide a contribution to understanding the formation of aneurysms. Other Information Published in: PAMM License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/pamm.202200004